Sosialisasi Pemanfaatan Media Sosial untuk mengedukasi remaja tentang bahaya perkawinan usia dini - Ati, Henny Dewi Laras; Prayoga, Ferdi; Prayoga, Fx Oby Edi; Daseka, Adhika Rio; Apriadi, Eko Aziz (CV. Tripe Konsultan, 2024)
Early marriage is a significant problem that impacts the health, education, and psychology of adolescents. The focus of this community service is to increase adolescent awareness about the dangers of early marriage through the use of social media. Topics include identifying causal factors, negative impacts, and effective educational strategies. The purpose of the community service is to disseminate accurate information about the risks of early marriage and motivate adolescents to continue their education. The methods used include developing educational content in the form of infographics, videos, and webinars, as well as publication through popular social media platforms such as Instagram, TikTok, and YouTube. The results of the community service show an increase in adolescent understanding of the dangers of early marriage and their active involvement in the campaign, demonstrating the effectiveness of social media as an educational tool that reaches a wide and interactive audience.